Does Percutaneous Kyphoplasty Have Better Functional Outcome Than Vertebroplasty in Single Level Osteoporotic Compression Fractures? A Comparative Prospective Study - F. Omidi-Kashani; F. Samini; E. G. Hasankhani; A. R. Kachooei; K. Z. Toosi; F. Golhasani-Keshtan (Journal of Osteoporosis)
Purpose. To evaluate the relative differences in surgical outcome of kyphoplasty (KP) versus vertebroplasty (VP) in the patients with single level refractory osteoporotic compression fractures (OCFs). Method. From August 2008 to May 2012, we intermittently treated 57 patients with single level OCF by PV and KP (Groups A and B, resp.). We used visual analogue scale (VAS) and short form 36 (SF36) questionnaire to measure functional recovery and followed them for six months. Independent samples t- and Kendall’s tau-b tests were for statistics. Results. In terms of age, number, and bone mineral density of the patients, there were no significant differences between the two groups. In both groups, VAS and SF-36 scores improved significantly and remained relatively stable throughout the follow-up period. We had 9 and 6 asymptomatic cement extravasations and 5 and 8 new vertebral fractures in Group A and B, respectively. In comparing the two groups, the results indicated that KP almost failed to show any significant higher effect relative to VP during this period. Conclusions. In considering the high cost of KP relative to VP in the developing countries like Iran, there is no logical reason to use KP in a single level refractory OCF in these regions.